Natural Photosensitizers in Clinical Trials - David Aebisher; Agnieszka Przygórzewska; Dorota Bartusik-Aebisher (Applied Sciences, 2024)
Photodynamic therapy (PDT) is a minimally invasive therapeutic method with high selectivity of action. It has gained great popularity in recent years as a new therapy for the treatment of cancer, but is also used in dermatology, ophthalmology, and antimicrobial treatment, among others. The therapeutic regimen involves the administration of a photosensitizer (PS) that selectively accumulates in tumor cells or is present in the blood vessels of the tumor prior to irradiation with light at a wavelength corresponding to the absorbance of the photosensitizer, leading to the generation of reactive oxygen species (ROS). Choosing the right PS is one of the most important steps in PDT and is crucial to the effectiveness of the therapy. Despite the many compounds discovered, the search for new molecules that could fulfill the functions of an optimal photosensitizer and improve the efficiency of PDT is still ongoing. Compounds of natural origin could contribute to achieving this goal. A number of photoactive substances as effective as synthetic photosensitizers have been described in various plant and fungal species. With the increasing identification of photoactive natural products, many new photosensitizers are expected to emerge. Some have already been clinically tested with promising results. In our work, we provide insights into this research and molecules, analyze their advantages and disadvantages, and point out gaps in current knowledge and future directions for their development. We also present natural photosensitizers not yet tested in clinical trials and point out future potential directions for their development.